Microstructure and mechanical properties of S217 nickel aluminum bronze alloy fabricated by wire arc additive manufacturing - Xiaoyu Cai; Baiyu Song; Bolun Dong; Sanbao Lin; Yuxuan Zhu (Virtual and Physical Prototyping)
Nickel aluminum bronze (NAB) is widely used in marine applications for its corrosion resistance and mechanical properties. Wire Arc Additive Manufacturing (WAAM) offers a cost-effective method for producing large-scale metal components, though research on WAAM-NAB is limited. This study investigated the microstructure, phase composition, and mechanical properties of WAAM-NAB. A single-wall component was successfully fabricated. The grains in the middle regions are larger than those in the top regions, and these grains have a weak texture. The alloy primarily contains α phases, retained β phases, and κ intermetallic phases (κIII, κII, κIV). The microhardness is uniform, averaging 181.2 HV0.3. Compared to cast NAB, WAAM-NAB shows superior mechanical properties, with minimal differences between vertical and horizontal directions. This research provides insights into the microstructure and performance of WAAM-NAB for marine applications.